Determine of soil properties and soil erosion at Universiti Malaysia Pahang, Pekan - Mohamed Fairos, Burkanudeen (2017)
A study on soil properties and soil erosion was conducted at Universiti Malaysia Pahang, Pekan. In order to determine the rate of erosion on two type of land surface and their soil properties, several related were soil testing conducted in the Geotechnical Laboratory, UMP. Testing that involved are a particle size distribution, moisture content, specific gravity, falling head, and fine analysis that were carried out in classify properties of the soil sample. The empty surface area is poorly graded sand with Cu < 4 and for vegetation surface area is well graded sand with Cu > 4. The specific gravity test showed that the soil sample empty surface and vegetation surface are 2.63mg/m3 and 2.58mg/m3 respectively. The moisture content for empty surface 1 and surface 2 are 7.37 % and 9 % respectively. The moisture content for vegetation surface 1 and surface 2 are 4.56 % and 5.83 % respectively. Soil erosion is a process of a portion of the soil profile or soil surface detachment to the ambient environment. Four major factors that affect erosion potential are soil characteristics, vegetative cover, topography and climate. The Revised Universal Soil Loss Equation (RUSLE) to predict the average annual soil loss rate at Campus Pekan, Universiti Malaysia Pahang. The result indicates that the average annual soil loss (A) for empty surface 1 and empty surface 2 is 9551.93ton/ha/yr and 9071.33ton/ha/yr respectively. For vegetation surface 1 and vegetation surface 2 is 59.67ton/ha/yr and 73.44ton/ha/yr respectively.